Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; cours; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales

Peau noire, masques blancs - Fanon, Frantz (Seuil, 1971)
La décolonisation faite, cet essai de compréhension du rapport Noir-Blanc a gardé toute sa valeur prophétique : car le racisme, malgré les horreurs dont il a affligé le monde, reste un problème d'avenir. Il est ici abordé et combattu de front, avec toutes les ressources des sciences de l'homme et avec la passion de celui qui allait devenir un maître à penser pour beaucoup d'intellectuels du tiers monde.
Première publication: 1952
Keywords: 1900-1999; 1950-1959; amériques; antilles; approches et analyses; colonialisme; cours; discipline; décolonialisme; europe; fem1000; femmes* noires; france; féminisme décolonial; har4600; histoire; postcolonialisme; premier cycle; psychanalyse; périodes historiques; racisme; régions géographiques; sciences; sciences humaines; systèmes d'oppressions